1997
DOI: 10.1103/physrevb.55.6180
|View full text |Cite
|
Sign up to set email alerts
|

Motion of a screw dislocation in a two-dimensional Peierls potential

Abstract: Motion of a screw dislocation in a crystal lattice occurs by kink pair formation in a two-dimensional Peierls potential. Employing the line-tension model of a dislocation, the saddle-point configuration of a nonplanar kink pair in three-dimensional space and the associated activation energy are calculated. The method is applied to a ͗111͘ screw dislocation in a bcc lattice assuming a threefold periodic sinusoidal Peierls potential in the ͑111͒ plane. In this potential the dislocation can nucleate a kink pair f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 20 publications
5
44
0
Order By: Relevance
“…This Peierls barrier is identified with the lowest energy path over the two-dimensional Peierls potential between two equivalent locations of the dislocation. This potential is, similarly as in [36], a function of the position of the intersection of the dislocation line with the {111} plane perpendicular to the corresponding 〈111〉 slip direction. In an unstressed crystal the Peierls potential possesses the three-fold rotation symmetry associated with the 〈111〉 direction as well as the periodicity of the corresponding {111} plane.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This Peierls barrier is identified with the lowest energy path over the two-dimensional Peierls potential between two equivalent locations of the dislocation. This potential is, similarly as in [36], a function of the position of the intersection of the dislocation line with the {111} plane perpendicular to the corresponding 〈111〉 slip direction. In an unstressed crystal the Peierls potential possesses the three-fold rotation symmetry associated with the 〈111〉 direction as well as the periodicity of the corresponding {111} plane.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is similar to that advanced in [36] but the novel concept is that the Peierls potential is considered to be a function of the full applied stress tensor. Since atomistic molecular statics calculations do not provide full information about the Peierls potential but give only the values of the Peierls stress, !…”
Section: Construction Of the Peierls Potential And The Peierls Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…Edagawa et al 19 suggested that the dislocation motion in TABLE I. Peierls stress ͑ P ͒ and core structure for a screw dislocation in Ta using the present multiscale approach, the FP-GFBC method, the EAM, and the modified generalized pseudopotential theory ͑MGPT͒.…”
mentioning
confidence: 99%